2022
DOI: 10.1111/trf.16962
|View full text |Cite
|
Sign up to set email alerts
|

The risk of thromboembolic events with early intravenous 2‐ and 4‐g bolus dosing of tranexamic acid compared to placebo in patients with severe traumatic bleeding: A secondary analysis of a randomized, double‐blind, placebo‐controlled, single‐center trial

Abstract: Background Screening for the risk of thromboembolism (TE) due to tranexamic acid (TXA) in patients with severe traumatic injury has not been performed in randomized clinical trials. Our objective was to determine if TXA dose was independently‐associated with thromboembolism. Study Design and Methods This is a secondary analysis of a single‐center, double‐blinded, randomized controlled trial comparing placebo to a 2‐g or 4‐g intravenous TXA bolus dose in trauma patients with severe injury. We used multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…While there were no differences in age between the three study groups, the bolus plus infusion group had more females (34%) versus single bolus (17%) versus double bolus (16%) ( p = 0.002; Table 1). Similarly, patients in this group had significantly higher median Injury Severity Score (ISS) 24–43 versus single bolus ISS 14–38 versus double bolus ISS (25, 16–34; p = 0.001). Patients who received bolus plus infusion had significantly higher rates of blunt injury, while the double bolus group had a higher proportion of severe abdominal injuries (Table 1).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…While there were no differences in age between the three study groups, the bolus plus infusion group had more females (34%) versus single bolus (17%) versus double bolus (16%) ( p = 0.002; Table 1). Similarly, patients in this group had significantly higher median Injury Severity Score (ISS) 24–43 versus single bolus ISS 14–38 versus double bolus ISS (25, 16–34; p = 0.001). Patients who received bolus plus infusion had significantly higher rates of blunt injury, while the double bolus group had a higher proportion of severe abdominal injuries (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…In view of these potential difficulties in adhering to the trial protocol, alternative dosing strategies have been investigated for trauma hemorrhage. [15][16][17][18][19] The prehospital STAMPP trial found a reduction in mortality with the use of two, sequential 1-g boluses, followed by a 1-g infusion when compared with placebo. 16 In addition, there are theoretical concerns about the prolonged exposure to TXA via an 8-hour infusion during the very dynamic phase of postinjury fibrinolysis.…”
Section: Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of plasmin is pertinent to major trauma because tranexamic acid is widely used to inhibit fibrinolysis and considered safe. However, there may be an increased risk of thromboembolic events in a subset of trauma patients, 23 warranting a further study to evaluate its interaction with innate hemostatic and immune systems.…”
Section: Fviii Activation and Inhibitionmentioning
confidence: 99%
“…5,6 While often debated, several studies have identified increased thrombotic risks associated with the administration of TXA to injured patients, particularly with higher doses. 7-12 Some data suggests the administration of TXA to patients with normal fibrinolysis may have a negative impact on mortality. 13,14 Further, a meta-analysis conducted in 2016 found both a dose-dependent risk of seizures in cardiothoracic surgery patients who received TXA.…”
Section: Introductionmentioning
confidence: 99%